Macroeconomic Policy : Does It Matter for Growth? The Role of Volatitliy - Fatás, Antonio; Mihov, Ilian (World Bank, Washington, DC, 2017)
Recent academic research has questioned the role of economic policy as a determinant of long term growth rates. While there seems to be a correlation between several policy variables and growth rates, this correlation disappears when controlling for other factors. As an example, the significance of key economic policy variables such as inflation or government size disappears if we account for the quality of institutions. This paper looks at recent empirical research that questions the conclusion that macroeconomic policy does not matter for growth. By looking at the volatility of economic policy (whether it is fiscal policy or exchange rates), the authors find that policy is still a relevant and robust explanatory variable of cross country differences in economic growth. These results have strong policy implications. Improvements in the conduct of macroeconomic policy can have beneficial growth effects even if institutional reforms are not taking place. These results do not deny the importance of institutional reforms. By setting the right institutions one can ensure the proper conduct of macroeconomic policy without having to rely on the 'quality' of the decision maker.